CLUSTERING PETANI BERDASARKAN DAMPAK COVID-19 YANG TERJADI PADA SEKTOR PERTANIAN - Dinda Ayu Lara Saky; Novia Apriana Jayanti; Wiwit Pura Nurmayanti (Seminar Nasional Official Statistics, 2020)
As the Covid-19 outbreak continues to spread around the world, it is important to impact the impact on the agricultural sector, both from a food supply and demand perspective. It is imperative to ensure that global and national food supplies continue to function in ensuring food supplies. Lepak hamlet, Lepak village, East Sakra sub-district, East Lombok, NTB is one of the areas with the most dominant farmer profession. Farmers in Lepak hamlet complain that their agricultural output continues to decline due to the Covid-19 outbreak which is increasingly spreading. And there are also farmers who have not felt the impact of the Covid-19 outbreak. Based on this, the researchers wanted to see the grouping of farmers in Lepak hamlet based on the impact of Covid-19 that occurred in the agricultural sector. Based on the results of the clustering hierarchy analysis, namely centroid linkage by taking 3 clustering, it can be concluded that the clustering of the impact of the Covid-19 impact on the agricultural sector in cluster 1, the number of members is 1 farmer, cluster 2 is 18 people, and cluster 3 there are 17 people. So, the clusters with the highest number of farmers are clusters 2 and 3. Based on the results of these clusters, it means that many farmers in Lepak hamlet feel disadvantaged by the Covid-19 outbreak, but not a few farmers also feel that Covid-19 has not significantly affected their agricultural output.